1978
DOI: 10.1111/j.1469-8749.1978.tb15222.x
|View full text |Cite
|
Sign up to set email alerts
|

The Neurological Manifestations of Chronic Inhalation of Leaded Gasoline

Abstract: SUMMARY Abnormal neurological signs were found in 46 of 50 children and adolescents chronically sniffing leaded gasoline. These abnormalities resolved within eight weeks in all but one case. Exaggerated deep reflexes, postural tremor and evidence of cerebellar dysfunction occurred in a highly significant number of patients. Forty‐nine had blood lead levels ≥40ug/dl. The mean blood lead levels were significantly higher in those with (a) abnormally brisk deep reflexes and (b) with evidence of cerebellar dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 36 publications
0
11
0
2
Order By: Relevance
“…It is well-known that tremor is a common manifestation of exposure to several neurotoxins, including lead, pesticides, and harmane, and that this tremor can be disabling (Seshia et al 1978;Valpey et al 1978;Louis et al 2002;Louis et al 2006). The tremor may take on several forms, including tremors that occur while the arms are at rest and kinetic tremors, which occur while the arms are performing purposeful movements such as eating or writing.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that tremor is a common manifestation of exposure to several neurotoxins, including lead, pesticides, and harmane, and that this tremor can be disabling (Seshia et al 1978;Valpey et al 1978;Louis et al 2002;Louis et al 2006). The tremor may take on several forms, including tremors that occur while the arms are at rest and kinetic tremors, which occur while the arms are performing purposeful movements such as eating or writing.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve case studies (Boeckx et al, 1977;Boor & Hurtig, 1977;Devathasan, Wan, Low, Wong, & Teoh, 1984;Edminster & Bayer, 1985;Ehyai & Freemon, 1983;Kamran & Bakshi, 1998;Keane, 1978;Kelly, 1975;Paulson & Waylonis, 1976;Rosenberg, Kleinschmidt-DeMasters et al, 1988;Tenenbein, deGroot, & Rajani, 1984;Valpey et al, 1978), seven clinical group reports (Comstock & Comstock, 1977;Fornazzari et al, 1983;Goodheart & Dunne, 1994;Hormes et al, 1986;King et al, 1981;Seshia et al, 1978;Streicher, Gabow, Moss, Kono, & Kaehny, 1981), and three case-control studies (Cairney et al, 2004c(Cairney et al, , 2005Maruff et al, 1998) were identified in the literature which suggested that recovery of neurological function may occur, beginning 1-2 weeks from cessation of VSM (see Table 2). Although significant recovery and normalization may be possible for some users, others experience residual or permanent neurological abnormalities that persist years after cessation and certainly with continued use (Boor & Hurtig, 1977;Cairney et al, 2004cCairney et al, , 2005Caldemeyer, Pascuzzi, Moran, & Smith, 1993;Devathasan et al, 1984;Edminster & Bayer, 1985;Ehyai & Freemon, 1983;Fornazzari et al, 1983;Goodheart & Dunne, 1994;Kamran & Bakshi, 1998;Keane, 1978;…”
Section: Recovery Of Neurological Abnormalitiesmentioning
confidence: 95%
“…Neurologic signs associated with VSM include staggering gait, loss of coordination, visual deterioration, tremor, abnormal reflexes, hearing loss, involuntary movements, inarticulate speech, and loss of smell (Boeckx et al, 1977;Cairney et al, 2004aCairney et al, , 2004cCairney et al, , 2005Ehyai & Freemon, 1983;Feldman et al, 1999;Goodheart & Dunne, 1994;King et al, 1981;Maruff et al, 1998;McGrath, 1986). Twelve case studies (Boeckx et al, 1977;Boor & Hurtig, 1977;Devathasan, Wan, Low, Wong, & Teoh, 1984;Edminster & Bayer, 1985;Ehyai & Freemon, 1983;Kamran & Bakshi, 1998;Keane, 1978;Kelly, 1975;Paulson & Waylonis, 1976;Rosenberg, Kleinschmidt-DeMasters et al, 1988;Tenenbein, deGroot, & Rajani, 1984;Valpey et al, 1978), seven clinical group reports (Comstock & Comstock, 1977;Fornazzari et al, 1983;Goodheart & Dunne, 1994;Hormes et al, 1986;King et al, 1981;Seshia et al, 1978;Streicher, Gabow, Moss, Kono, & Kaehny, 1981), and three case-control studies (Cairney et al, 2004c(Cairney et al, , 2005Maruff et al, 1998) were identified in the literature which suggested that recovery of neurological function may occur, beginning 1-2 weeks from cessation of VSM (see Table 2). Although significant recovery and normalization may be possible for some users, others experience residual or permanent neurological abnormalities that persist years after cessation and certainly with continued use …”
Section: Recovery Of Neurological Abnormalitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Different components in petrol have been suggested to cause polyneuropathy, either tetraethyl lead [46], n-hexane [47][48][49][50] or maybe both [51] . Besides petrol and diesel exposure, 7 male cases and 4 referents added exposure to jet fuel and jet engine exhausts in the questionnaire with COR = 6.73 (95% CI = 1.54-33.21).…”
Section: Discussionmentioning
confidence: 99%